1994
DOI: 10.1677/joe.0.1420407
|View full text |Cite
|
Sign up to set email alerts
|

Biological effects of prostate specific antigen as an insulin-like growth factor binding protein-3 protease

Abstract: Prostate specific antigen (PSA) is an insulin-like growth factor (IGF) binding protein-3 (IGFBP-3) protease found in seminal plasma and produced by prostatic epithelial cells (PC-E) in vivo. We examined the effects of PSA-proteolysis of IGFBP-3 on the affinity of IGFBP-3 fragments for IGFs and on the mitogenic action of IGFs on PC-E. Recombinant human IGFBP-3 was cleaved by PSA, then incubated with 125I-IGF-I or -II in the presence of varying concentrations of unlabelled peptides, and then cross-linking electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
123
0
6

Year Published

1996
1996
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 252 publications
(137 citation statements)
references
References 18 publications
6
123
0
6
Order By: Relevance
“…(i) PSA acts as mitogen to breast tissue through of TGF-b (transforming growth factor b), a known mitogen of breast tissue [29] (ii) PSA degrades fibronectin and laminin, the cellular matrix proteins, thereby facilitating local invasion [30] (iii) It increases IGF-1, a proven mitogen of breast tissue [31] (iv) It degrades IGFBP-3, which normally induces apoptosis in breast tissue and its degradation by PSA stimulates tumour progression [32].…”
Section: Rank Of Serum Tpsa Rank Of Serum Testosteronementioning
confidence: 99%
“…(i) PSA acts as mitogen to breast tissue through of TGF-b (transforming growth factor b), a known mitogen of breast tissue [29] (ii) PSA degrades fibronectin and laminin, the cellular matrix proteins, thereby facilitating local invasion [30] (iii) It increases IGF-1, a proven mitogen of breast tissue [31] (iv) It degrades IGFBP-3, which normally induces apoptosis in breast tissue and its degradation by PSA stimulates tumour progression [32].…”
Section: Rank Of Serum Tpsa Rank Of Serum Testosteronementioning
confidence: 99%
“…IGFBP proteases have been detected for IGFBP-3 in prostatic cancer (Cohen et al, 1994) and IGFBP-4 in osteoblast cell systems (Lalou et al, 1994). A serine protease that specifically degrades IGFBP-5 in fibroblasts has been reported (Nam et al, 1994).…”
Section: Immunohistochemistrymentioning
confidence: 99%
“…In other studies, men with prostate cancer were said to have higher serum IGF-1 levels compared to men with BPH or aged-matched normal men. [31][32][33] A possible explanation for the disparity in our study may be because men with prostate cancer in this study were about a decade older than those with BPH. Serum IGF-1 level declines with age.…”
Section: Discussionmentioning
confidence: 61%
“…7 Many unanswered questions remain regarding serum IGF-1 and IGFBP-3 levels and risk of prostate cancer. [31][32][33] For example, Kanety et al 32 actually demonstrated lower serum IGF-1 concentrations in patients with prostate cancer; however, their population was composed mainly of patients with advanced disease, who therefore may have had diminished nutritional status leading to lower 35 reported that plasma IGFBP-3 levels were found to be highest in healthy subjects, followed by patients with localized prostate cancer and patients with lymph node metastases while the lowest levels were found in patients with skeletal metastases. The findings from the Arab population with a low incidence of prostate cancer are in agreement with those of Shariat et al 2002.…”
Section: Discussionmentioning
confidence: 99%